2012
DOI: 10.1590/s0102-695x2012005000008
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating effect of seeds of Adenanthera pavonina aqueous extract in neuropathic pain in streptozotocin-induced diabetic rats: an evidence of neuroprotective effects

Abstract: Abstract:The aim of present study was to investigate the attenuating effects of Adenanthera pavonina L., Leguminosae-Mimosaceae seeds aqueous extract (APSAE), in streptozotocin (STZ)-induced diabetic neuropathy in rats. APSAE (50, 100 and 200 mg/kg per day) was given to diabetic rats for twelve weeks. Cold and hot water tail immersion tests, photoactometer and Rota-rod tests were performed to assess degree of colder, thermal, spontaneous motor activity and motor co-ordination changes respectively at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Adenanthera pavonina (Madatiya –Sinhala, Circassian bean–English) belonging to the family Fabaceae; used in traditional herbal medicine for a variety of diseases including diabetes, lipid disorders, diarrhea, hemorrhage, and as an anti-inflammatory agent [5]. Phytochemical investigations of the plant have identified many compounds which are steroids, glycosides, alkaloids, saponins, polysaccharides, fatty acids and various amino acids [5, 6] with no claims of any of the above compounds to be active as an antidiabetic compound. Studies performed on the seed and leaf extracts on rat models have shown to possess hypoglycemic and antihyperglycemic activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Adenanthera pavonina (Madatiya –Sinhala, Circassian bean–English) belonging to the family Fabaceae; used in traditional herbal medicine for a variety of diseases including diabetes, lipid disorders, diarrhea, hemorrhage, and as an anti-inflammatory agent [5]. Phytochemical investigations of the plant have identified many compounds which are steroids, glycosides, alkaloids, saponins, polysaccharides, fatty acids and various amino acids [5, 6] with no claims of any of the above compounds to be active as an antidiabetic compound. Studies performed on the seed and leaf extracts on rat models have shown to possess hypoglycemic and antihyperglycemic activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…The treated group showed an increased tail flick latency significantly when compared with pregabalin and reduced superoxide anion and total calcium levels which gave evidence of neuroprotective effects [145]. …”
Section: Resultsmentioning
confidence: 99%
“…Nigella sativa , Ocimum sanctum , Teucrium polium , Phyllanthus amarus, and Sesbania sesban also have been tested in single studies to ameliorate neuropathic pain [141145]. …”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the pre-treatment with the seed extracts possess beneficial antiinflammatory effects by suppressed nitric oxide production and superoxide anion generation, cell death, and nuclear fragmentation by inhibiting the H 2 O 2 mediated generation of oxidative damage in rat peritoneal macrophages, suggesting that the extract has a cytoprotective property against intracellular peroxide production. Pandhare et al (2012b) evaluated the ameliorative effect of seeds of A. pavonina aqueous extract in attenuating neuropathic pain in streptozotocin-induced diabetic rats during twelve weeks of treatment. Diabetic rats orally received the test extract in 50, 100, or 200 mg/kg per day and pregabalin as a standard drug.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%